Fire Severity Influences Ecophysiological Responses of Pinus pinaster Ait - Niccoli, Francesco; Esposito, Assunta; Altieri, Simona; Battipaglia, Giovanna (Frontiers in Plant Science, 2019)
The effect of fire severity on Pinus pinaster growth and ecophysiological responses was evaluated in four burned sites of Vesuvio National Park, Southern Italy. After the wildfire of 2017, when over 1300 hectares of vegetation, mainly P. pinaster woods, were destroyed, four sites were selected according to the different degree of fire severity and a multidisciplinary approach based on tree rings, stable isotopes and percentage of crown scorched or consumed was applied. All the sampled trees in the burned sites showed a decrease in tree growth in 2017, in particular in the latewood at high-severity site. The dendrochronology analyses showed that several individuals experienced and endured higher fire severity in the past compared to 2017 fire. Further δ13C and δ18O underlined the ecophysiological responses and recovery mechanisms of P. pinaster, suggesting a drastic reduction of photosynthetic and stomata activity in the year of the fire. Our findings demonstrated that P. pinaster growth reduction is strictly linked to the percentage of crown scorch and that even trees with high level of crown scorched could survive. In all the burned sites the high temperatures and the time of exposure to the flames were not sufficient to determine the death of the cambium and all the trees were able to complete the 2017 seasonal wood formation. This data can contribute to define guidelines to managers making post-fire silvicultural operations in pine forest stands in the Mediterranean Basin.